A Novel Cause of Biliary Peritonitis after Endoscopic Retrograde Cholangiopancreatography: Case Report and Literature Review - Andrija Karačić; Paula Batur; Domagoj Štritof; Taro Fukui; Branko Bakula; Inka Kekez (Case Reports in Gastrointestinal Medicine)
Background. Endoscopic retrograde cholangiopancreatography (ERCP) can lead to several complications such as duodenal or bile duct perforation. The incidence of pneumoperitoneum post-ERCP is rarely seen (<1%) and is associated with perforations of the duodenum or common bile duct in therapeutic ERCP after sphincterotomy. In this case, we disclose a novel cause of biliary peritonitis after ERCP. Case Presentation. A 65-year-old man presented with abdominal pain and distended abdomen after uneventful ERCP with sphincterotomy. An abdominal computed tomography (CT) was performed whose finding indicated duodenal perforation. The patient was rushed to an emergency laparotomy where only a rupture of an otherwise normal subcapsular intrahepatic bile duct was found. The surrounding liver parenchyma was healthy. The cause of this condition was probably post-ERCP pneumobilia and the increase of pressure in the biliary tract. Conclusions. This is the first case in literature describing the rupture of a subcapsular healthy bile duct as cause of biliary peritonitis after ERCP. This case also suggests that in the management of post-ERCP complications, the cooperation of radiologists and surgeons is vital for the patient’s wellbeing.